PERCEPTIONS OF SHISHA SMOKING AMONG UNIVERSITY STUDENTS IN PAKISTAN - Zahid Masood; Khurram Sohail (Journal of University Medical & Dental College, 2013)
ABSTRACT OBJECTIVES: To study the perceptions of Shisha smoking among university students in Pakistan. METHODS: It was descriptive cross – sectional study conducted from October 2011 to March 2012 at four different public and private sector Universities at Lahore, Rawalpindi, Faisalabad and Gujrat in province of Punjab. After approval from ethical committees of concerned universities, 1000 university students participated in the study through simple random sampling technique. There were 750 males and 250 female students studying in graduate and post graduate programs. Informed consent was taken from participants. There remains a possibility of response and selfselection bias. The Inclusion criterion was students between 18 to 30 years. They were selected from B.S, BBA, MBA, M.Com, M.A (English), and MSc (Psychology) departments. All students were interviewed on a structured questionnaire which was pretested. Each student was allowed to complete the questionnaire freely and without consultation with other fellow students. Finally data was tabulated and analysis was done. RESULTS: In our study curiosity and social trend emerged as the most common factors for initiation of shisha. Respiratory disease was the most commonly cited health effect. In the study 440 males (59.22%) and 54 females (22%) were using Shisha smoke. Seventy five% university students were aware of at least one hazard of shisha smoking. Fifty two % knew that shisha smoke causes lung cancer. Despite knowing its fatal effect 74% strongly agreed that they use shisha smoke as part of fashion. Thirty eight % believed that shisha smoke was good source of stress relief. Only 14% believed that shisha has addictive properties. CONCLUSIONS: It is concluded that Shisha smoking is injurious to health. It has become a fashion and snobbery among our university students. It has become a status symbol in our society. Our youngsters take it as a fashion, stress reliever and later they become addicted to it. We conclude with the disturbing observation that shisha smoking is highly prevalent among urban university students in Pakistan. The knowledge of university students regarding the hazards of habitual shisha smoking is alarmingly low and the majority considers the practice to be safer than cigarette smoking. These results not only unlock new avenues for targeted research on the issue but should also serve as an alarm call for the public health authorities in the country. A similar study with larger sample size may be conducted in rural set up where around 70% of population resides and literacy rate is very low.